Love Cards: Media Orang Tua Menerapkan Perilaku Hidup Bersih dan Sehat pada Anak Usia Dini di Masa Pandemi COVID-19 - Zuniarsih, Zuniarsih; Maemonah, Maemonah; Dwi Selvi, Issaura (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
The impact of COVID-19 has had a major impact on the protection of children's health. Parents need to supervise children in implementing clean and healthy living behavior to avoid COVID-19. The purpose of this research is to use love cards as a form of activity to increase enthusiasm for protecting children's health. This research refers to the type of quantitative quasi-experimental research that applies one group pre-test-post-test design. Data collection techniques using interviews, questionnaires, and documentation. The subject of this study involved 20 parents who provide the results of children's development achievements. The results showed that the application of clean and healthy living behavior during the pre-test was 25%, and after being given treatment using love cards, the percentage was 85%. There was a significant increase from pre test to post test by 60%. That study using love cards have a good effect on increasing the application of clean and healthy living behavior (PHBS) in early childhood.